Using Data Technology Platforms to Deliver Stakeholder Value in Healthcare - Daniel Rees (Technology | Amplify, 2024)
Daniel J. Rees, Roderick A. Thomas, Victoria Bates, and Gareth Davies examine the transformational impact that healthcare-related technologies (e.g., AI, wearable sensors, clinical and genetic data) have on the healthcare and pharmaceutical industries. These technologies can potentially transform healthcare business processes, resulting in faster, more efficient decision-making, human-error reduction, and accelerated product development cycles that can lead to faster product launches. The authors gained insights from 48 senior managers in healthcare and pharmaceutical organizations to both identify best practices and understand the challenges related to using healthcare-related technologies and data-centric decision-making to deliver value to stakeholders. Best practices, such as governance (memorandum of understanding), incentives (monetary and nonmonetary), scalability, and collaboration between pharmaceutical makers and technology companies, are identified as key enablers. Such practices enable stakeholders to mitigate challenges like culture (trust, reputation, time, risk aversion), governance (contracts), and scalability. The article concludes with recommendations to ensure the right individuals choose tools and processes that can lead to successful partnerships and transformational initiatives for the benefit of patients, society, and the wider economy.